2018
DOI: 10.1111/1759-7714.12893
|View full text |Cite
|
Sign up to set email alerts
|

Capn4 promotes esophageal squamous cell carcinoma metastasis by regulating ZEB1 through the Wnt/β‐catenin signaling pathway

Abstract: BackgroundCapn4 and ZEB1 play important roles in the metastasis of several types of cancer. However, the roles and relationship of Capn4 and ZEB1 in esophageal squamous cell carcinoma (ESCC) remain unclear.MethodsESCC tumor tissues and corresponding normal esophageal epithelial tissues were obtained from 86 patients undergoing resection surgery at the Department of General Surgery, First Affiliated Hospital of Chinese PLA General Hospital from 2012 to 2017. Cell migration and invasion were examined via quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These data suggest that miR-124 expression may be dysregulated under high-glucose conditions, where it serves a favorable role in attenuating inflammation or kidney injury. Data from these two previous studies also showed that miR-124 expression could be negatively regulated by lnc-NEAT1 (6,7), such that miR-124 can in turn directly bind to the Capn1 mRNA, which is known to modulate cell physiology through the Wnt/β-catenin pathway (8)(9)(10)(11)(12)(13)(14)27,28). Capn1 has been reported to increase the plasma glucose level, where the Wnt/β-catenin pathway can affect renal tubulointerstitial transdifferentiation during DN (29,30).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These data suggest that miR-124 expression may be dysregulated under high-glucose conditions, where it serves a favorable role in attenuating inflammation or kidney injury. Data from these two previous studies also showed that miR-124 expression could be negatively regulated by lnc-NEAT1 (6,7), such that miR-124 can in turn directly bind to the Capn1 mRNA, which is known to modulate cell physiology through the Wnt/β-catenin pathway (8)(9)(10)(11)(12)(13)(14)27,28). Capn1 has been reported to increase the plasma glucose level, where the Wnt/β-catenin pathway can affect renal tubulointerstitial transdifferentiation during DN (29,30).…”
Section: Discussionmentioning
confidence: 96%
“…Capn1 belongs to the Capn family of protease enzymes, the silencing of which can relieve adipose tissue inflammation and fibrosis in a diet-induced mouse model of obesity. Capns are able to regulate the β-catenin (CTNNB) signaling pathway by modifying N-terminal truncation of β-catenin to regulate a multitude of cellular functions, including proliferation and epithelial-mesenchymal transition (9)(10)(11)(12)(13)(14). Therefore, it was hypothesized that lnc-NEAT1 is involved in mediating the DN pathology, such that its potential regulatory effects may include miR-124 and the Capn1/CTNNB signaling pathway downstream.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study confirmed that ZEB1-induced miR-99b/let-7e/miR-125a cluster promotes invasion and metastasis in ESCC ( 27 ). ZEB1 is also associated with Capn4-promoted ESCC metastasis ( 28 ). Recent research suggested repressing the biogenesis of circ-DOCK5 to facilitate metastasis in ESCC via a positive feedback loop with TGF-β ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ZEB1 is not only highly expressed in cases with CC, but also overexpressed in cases with diseases such as esophageal squamous cell carcinoma, liver cancer, and cutaneous squamous cell carcinoma, which suggests that it may have extensive carcinogenicity. [30][31][32] An increasing number of scholars have shown interest in studying the influence of miR-139-5p on gynecologic tumors, and have published many studies. For instance, Liu et al 33 have reported that miR-139-5p can suppress the viability and migration of endometrial carcinoma cells through targeted inhibition on HOXA10.…”
Section: Discussionmentioning
confidence: 99%